Macranthoidin B restrains the epithelial-mesenchymal transition through COX-2/PGE2 pathway in endometriosis - Ding, Yi; Yang, Xiaoqian; Wei, Qinghua; Bi, Xuanming; Zhang, Yuxin; Ma, Yuxia; Yang, Meisen; Xu, Xiaoyu; Li, Cong; Wang, Qin; Chen, Yi (Frontiers in Pharmacology, 2024)
IntroductionMacranthoidin B is one of the primary and unique triterpenoid saponin metabolites from Lonicera macranthoides Hand. –Mazz, which is used to treat endometriosis (EMS) in traditional Chinese medicine. However, the effect of macranthoidin B remains unknown in EMS. This study aimed to elucidate the effect and mechanism of macranthoidin B in EMS.MethodsUsing rat autograft EMS model, the volume of ectopic endothelium, the histopathology, serum E2 and PROG were evaluated after macranthoidin B’s treatment. In primary endometriotic stromal and HEC1-B cells, the invasion and metastasis were assessed by scratch wound and Transwell tests. The epithelial-mesenchymal transition and COX-2/PGE2 pathway were examined in vivo and in vitro. Macranthoidin B were combined with LPS or celecoxib.ResultsIn a rat autograft EMS model, macranthoidin B suppressed ectopic lesion volume, improved histopathological morphology, and regulated serum estradiol (E2) and progesterone (PROG) levels. Additionally, macranthoidin B inhibited invasion and metastasis of primary endometriotic stromal cells and HEC1-B cells. Mechanistically, macranthoidin B suppressed COX-2/PGE2 pathway and epithelial-mesenchymal transition both in vivo and in vitro. LPS, the COX-2/PGE2 pathway activator, showed the promotion of epithelial-mesenchymal transition, invasion and metastasis. Macranthoidin B exhibited the antagonistic effects against LPS. Celecoxib, the COX-2/PGE2 pathway inhibitor, restrained the epithelial-mesenchymal transition, invasion and metastasis. This effect of celecoxib was enhanced by macranthoidin B.Discussion Macranthoidin B prevents epithelial-mesenchymal transition through COX-2/PGE2 pathway in EMS. It will facilitate the macranthoidin B’s development and broaden its potential application.